Study of Clinical Profile, Risk Factors, Pattern of Drug Resistance and Treatment Outcome in Previously Treated Patients of Pulmonary Tuberculosis - Shehnas P.A., Uday C. Kakodkar (International Journal of Innovative Research in Medical Science, 2017)
Introduction: Tuberculosis has been a scourge of mankind from times immemorial and still an important public health problem in India and other developing countries. An estimated 3.3% of new cases and 20% of previously treated cases have MDR-TB: these levels sadly have remained unchanged in recent years. In 2014 there were estimated 480,000 new cases of MDR-TB and approximately 190,000 deaths from MDR-TB worldwide. Materials and Method: The sputum smear and culture for Mycobacterium Tuberculosis and drug sensitivity tests were performed in 67 patients who had received anti-TB treatment for more than 4 months as retreatment regimen. The sputum smear was positive for AFB in all the patients, the sputum culture was done by LJ method and the sensitivity to Streptomycin, INH, Rifampicin and Ethambutol was done. The clinical profile, pattern of drug resistance, probable risk factors for development of drug resistance and the treatment outcome was analyzed in the study group. Results: 65 patients of drug resistant PTB were included in the final analysis. 94%patients had moderately advanced to far advanced disease on chest radiograph.. Irregular anti-TB treatment was the contributory factor in the development of drug resistant PTB in two thirds of the patients. The resistance to Rifampicin, INH, Streptomycin and Ethambutol was seen in 89.23%, 81.54%, 60% and 46.15 % patients respectively. MDR – TB strains were isolated in 53(81.54%) patients. 24 patients(36.92%) had bacilli resistant to all the 4 first line drugs .The default rate was 27.59% and the cure rate was 59.05% in the study group. The mortality in the study group was 13.85%. Conclusions: The high level of resistance seen to the first line drugs amongst previously treated patients of PTB is a subject of major concern and this study emphasizes the need for a concerted and integrated efforts by physicians to treat the patients with drug sensitive bacilli with all the seriousness it deserves to prevent emergence of resistant TB.